Opposing Spatially Segregated Function of Endogenous GDNF-RET Signaling in Cocaine Addiction - Daniel R. Garton; Giorgio Turconi; Vilma Iivanainen; Jaan-Olle Andressoo (Biomolecules, 2023)
Cocaine addiction is a serious condition with potentially lethal complications and no current pharmacological approaches towards treatment. Perturbations of the mesolimbic dopamine system are crucial to the establishment of cocaine-induced conditioned place preference and reward. As a potent neurotrophic factor modulating the function of dopamine neurons, glial cell line-derived neurotrophic factor (GDNF) acting through its receptor RET on dopamine neurons may provide a novel therapeutic avenue towards psychostimulant addiction. However, current knowledge on endogenous GDNF and RET function after the onset of addiction is scarce. Here, we utilized a conditional knockout approach to reduce the expression of the GDNF receptor tyrosine kinase RET from dopamine neurons in the ventral tegmental area (VTA) after the onset of cocaine-induced conditioned place preference. Similarly, after establishing cocaine-induced conditioned place preference, we studied the effect of conditionally reducing GDNF in the ventral striatum nucleus accumbens (NAc), the target of mesolimbic dopaminergic innervation. We find that the reduction of RET within the VTA hastens cocaine-induced conditioned place preference extinction and reduces reinstatement, while the reduction of GDNF within the NAc does the opposite: prolongs cocaine-induced conditioned place preference and increases preference during reinstatement. In addition, the brain-derived neurotrophic factor (BDNF) was increased and key dopamine-related genes were reduced in the GDNF cKO mutant animals after cocaine administration. Thus, RET antagonism in the VTA coupled with intact or enhanced accumbal GDNF function may provide a new approach towards cocaine addiction treatment.